2011
DOI: 10.1038/gt.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

Effective and safe gene-based delivery of GLP-1 using chitosan/plasmid-DNA therapeutic nanocomplexes in an animal model of type 2 diabetes

Abstract: Glucagon-like peptide-1 (GLP-1) is an incretin hormone that regulates blood glucose level post-prandially. It has been proposed that GLP-1 can be used in type 2 diabetes (T2D) mellitus treatment because of its insulinotropic action. Despite its remarkable advantages, GLP-1 suffers the disadvantage of an extremely short half-life owing to its degradation by the dipeptidyl peptidase IV protease. One way of overcoming this drawback is GLP-1 gene delivery. Here we show effective and safe gene-based delivery of GLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 68 publications
0
30
0
1
Order By: Relevance
“…Decreased blood glucose levelMandke and Singh (2012)[27] Cationic nanomicelles comprising chitosanGLP-1-plasmid DNAIntestinesSubcutaneous injection in dorsal or intramuscular injection in hind legsEnhanced insulin secretion. Improved glucose toleranceJean et al (2011)[28] ABPExendin-4 plasmid DNAWhole bodyIntravenous injectionDecreased blood glucose levelKim et al (2012)[29] Ultrasound-targeted microbubbleANGPTL8 plasmid DNAWhole bodyIntravenous injectionPromoted the proliferation of aged β cells and expandedthe β cell mass. Improved glucose tolerance andincreased the fasting blood insulin levelChen et al (2006)[30]

Abbreviations : PDX-1: pancreas/duodenum homeobox protein 1; ISL-1: insulin gene enhancer protein-1; GLP-1: glucagon-like peptide-1; DNA: deoxyribonucleic acid; AAV: adeno-associated viral vector; HGF/NK1: N and K1 domains of hepatocyte growth factor; REG3: regenerating islet-derived protein 3; IL-2: interleukin-2; PEI: polyethylenimine; ATR3: activating transcription factor 3; ER: endoplasmic reticulum; IL-4: interleukin-4; IL-10: interleukin-10; ABP: arginine-grafted bioreducible polymer; ANGPTL8: angiopoietin-like protein 8.

10.1080/20022727.2017.1341758-F0001Figure 1.Viral and non-viral vectors for the treatment of renal fibrosis in vivo .
…”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased blood glucose levelMandke and Singh (2012)[27] Cationic nanomicelles comprising chitosanGLP-1-plasmid DNAIntestinesSubcutaneous injection in dorsal or intramuscular injection in hind legsEnhanced insulin secretion. Improved glucose toleranceJean et al (2011)[28] ABPExendin-4 plasmid DNAWhole bodyIntravenous injectionDecreased blood glucose levelKim et al (2012)[29] Ultrasound-targeted microbubbleANGPTL8 plasmid DNAWhole bodyIntravenous injectionPromoted the proliferation of aged β cells and expandedthe β cell mass. Improved glucose tolerance andincreased the fasting blood insulin levelChen et al (2006)[30]

Abbreviations : PDX-1: pancreas/duodenum homeobox protein 1; ISL-1: insulin gene enhancer protein-1; GLP-1: glucagon-like peptide-1; DNA: deoxyribonucleic acid; AAV: adeno-associated viral vector; HGF/NK1: N and K1 domains of hepatocyte growth factor; REG3: regenerating islet-derived protein 3; IL-2: interleukin-2; PEI: polyethylenimine; ATR3: activating transcription factor 3; ER: endoplasmic reticulum; IL-4: interleukin-4; IL-10: interleukin-10; ABP: arginine-grafted bioreducible polymer; ANGPTL8: angiopoietin-like protein 8.

10.1080/20022727.2017.1341758-F0001Figure 1.Viral and non-viral vectors for the treatment of renal fibrosis in vivo .
…”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%
“…Several studies have reported the treatment effects of GLP-1 transgene delivery to the intestines using non-viral vectors in animal models of diabetes mellitus in vivo [24,28,54]. Delivery of GLP-1 transgene with cationic nanomicelles comprising chitosan or arginine-grafted bioreducible polymer to the intestines was reported to have insulinotropic effects in animal models of diabetes mellitus [24,28,54].…”
Section: Transgenes For the Treatment Of Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, addition of albumin to polyplexes improves penetration through the sputum and provides transfection in CF (Di Gioia, et al, 2008). Bioadhesive and pH-responsive properties of chitosan nanoparticles, along with its lack of toxicity, can also benefit delivery of gene therapies (Agnihotri, et al, 2004), including oral gene delivery applications such that of coagulation factor VIII in a hemophilia mouse model (Dhadwar, et al, 2010) or glucagon-liked peptide 1 (GLP-1) to reduce blood glucose in diabetes (Jean, et al, 2011).…”
Section: Gene Therapymentioning
confidence: 99%
“…It was shown that feeding of factor VIII-encoding chitosan-DNA NP to hemophilia A mice resulted in increased factor VIII plasma levels (6,15) and that oral application of erythropoietin-encoding chitosan-DNA NP led to a significant increase of hematocrit levels (8). In rodent models of diabetes, chitosan-DNA NP encoding insulin or glucagon-like peptide 1 were able to decrease blood glucose concentrations (23,31,32). In addition, there is potential for chitosan-DNA NP to be used for immune modulation.…”
mentioning
confidence: 99%